GLOBAL FINANCIAL INSTITUTIONS, DEBT CRISIS, AND RESOURCE CONTROL DEBATES IN NIGERIA - Temple C. Nwambuko; Ernest Ositadimma Ugwu; Ogbonnaya N. Udoh (ESUT JOURNAL OF SOCIAL SCIENCES, 2026)
This study examines the interplay between global financial institutions (GFIs), debt accumulation, and resource control debates in Nigeria, with a focus on the mediating role of international administrative frameworks (IAFs). The research adopts a descriptive survey design, collecting data from 380 respondents comprising policymakers, academics, and public administrators. Data were analyzed using both descriptive statistics (frequencies, percentages, mean scores, and standard deviation) and inferential statistics, including Pearson Product-Moment Correlation and multiple regression analysis, to test hypothesized relationships at a 0.05 significance level. Findings indicate that GFIs significantly influence Nigeria’s debt management strategies, and debt accumulation is strongly associated with resource control demands in oil-producing states. International administrative frameworks were found to partially mediate the relationship between GFIs and resource control debates, enhancing fiscal governance while shaping the execution of debt policies. Correlation analysis revealed strong positive associations among all variables, while regression results demonstrated that the inclusion of IAFs increased the explained variance in resource control demands from 34% to 49%, indicating a substantial mediating effect. The study concludes that sustainable fiscal governance in Nigeria requires balancing the influence of external financial institutions with equitable domestic resource management. Policy recommendations include strengthening fiscal federalism, integrating international administrative standards with local institutions, enhancing transparency in debt and revenue management, promoting stakeholder engagement, and building administrative capacity. The findings contribute to understanding the political economy of debt and resource control in Nigeria, highlighting the importance of institutional frameworks in mediating external financial pressures and domestic fiscal tensions.